(untitled) (Journal of Nepal Geological Society, 2004)
Rock eval pyrolysis is instrumental in rapid evaluation of maturation and source rock characteristics by providing vital information about the quantity, type and thermal maturity of organic matter. The Ib-Valley coal deposits have been characterized for their source rock potentiality and thus to explore the chances of their involvement in hydrocarbon generation.